(untitled) (International Journal of Food and Nutritional Sciences, 2023)
A diverse environment of microorganisms in the gut, holding most of our bacterial microorganisms. The gut environment has a symbiotic association with the surrounding organism, and an equilibrium and variety of bacteria support health of an individual. When variety of gut bacteria reduces, results in gastrointestinal and mental distress. This path of interaction is identified as the microbiome–gut–brain axis. Strategies such as probiotic supplementation that influence microbiome also improve both gut and mind illnesses. Current evidence recommends that Yogic practices like Dhauti, Vasti improves the variety of microbiome, which may be positively affects both the gut and mind. The purpose of this article is to elucidate the pathway of the microbiome–gut–brain axis and suggests the role of specific Yogic practice on gut microbiome